Fluoride Ion Uptake by Synthetic Apatites - Ahmed Yehia; Khaled Ezzat (Adsorption Science & Technology)
Fluoride uptake by synthetic apatites from aqueous solutions was studied as a function of fluoride ion concentration. The phosphate minerals synthesized and considered included different varieties of phosphate minerals of the apatite group such as hydroxy-, carbonato- and chloro-apatite, all being precipitated at the boiling point. An ion-selective electrode technique was used for fluoride ion analysis in the adsorption experiments and electrokinetic measurements were utilized to delineate specific adsorption effects. The results suggest that, at low fluoride ion concentrations, a fluoroapatite-type compound may form on the apatite surface via the chemisorption of fluoride ions at calcium sites; at high fluoride ion concentrations, calcium fluoride appears to form at the apatite surface via a surface-precipitation phenomenon. The formation of CaF 2 on the surface of fluoride ion-treated apatite was further substantiated by FT-IR spectroscopic measurements, which clearly demonstrated a metathetic exchange with phosphate from the apatite lattice during the surface precipitation process.